Physical climate change risks and the sovereign creditworthiness of emerging economies - Hannes Böhm (Halle Institute for Economic Research (IWH), 2020)
I show that rising temperatures can detrimentally affect the sovereign creditworthiness of emerging economies. To this end, I collect long-term monthly temperature data of 54 emerging countries. I calculate a country's temperature deviation from its historical average, which approximates present day climate change trends. Running regressions from 1994m1-2018m12, I find that higher temperature anomalies lower sovereign bond performances (i.e. increase sovereign risk) significantly for countries that are warmer on average and have lower seasonality. The estimated magnitudes suggest that affected countries likely face significant increases in their sovereign borrowing costs if temperatures continue to rise due to climate change. However, results indicate that stronger institutions can make a country more resilient towards temperature shocks, which holds independent of a country's climate.
urn:nbn:de:gbv:3:2-121581
Keywords: G15; H63; O13; Q54; Q56; 330; climate risks; sovereign creditworthiness; international finance; emerging market economies; institutions